The special effect of interest rate cuts on housing prices - Lin, Che-Chun; Tsai, I-Chun (Journal of Business Economics and Management, 2021)
This study uses theoretical models and empirical research to explain that interest rates affect the structure of housing price formation and correction rather than affect the price alone. In particular, when interest rates are substantially reduced, the correction of housing prices toward fundamentals is absent; in other words, a housing bubble is likely to occur. This study first illustrates a model for explaining home price behavior. Data from the Case-Shiller U.S. National Home Price Index between January 1975 and August 2020 are adopted to observe the behavior of home prices. The empirical results show that the correction and bubble behavior of U.S. home prices have exhibited significant structural changes. Variation in money supply fails to explain the structural changes, however, interest rate variation can significantly affect the structural changes. According to the results, when interest rates rise or fall slightly, the correction of home prices toward the equilibrium value is significant. However, when interest rates fall substantially, the bubble behavior of home prices is significant. For governments that adopt low interest rates to revitalize the economy, the results of this study provide special reference values. Governments should provide additional intervention in housing markets when an extremely low interest rate exists.